Research advances of caspases in acute kidney injury - Hao-nan Duan; Xiao-yan Wang (Editorial Department of Journal of Clinical Nephrology, 2024)
As a diverse group of conserved cysteine-containing aspartic protein hydrolases in cytoplasm, caspases are associated with apoptosis and inflammation. After an activation of macromolecular signaling complexes, they ultimately lead to programmed cell deaths of apoptosis and pyroptosis, depending on specific types of activated caspases. This review summarized the mechanisms of caspase-mediated apoptosis and pyroptosis in different types of acute kidney injuries (AKI) induced by sepsis, ischemia/reperfusion, drugs and rhabdomyolysis. The goal was to understand the importance of those regulators in AKI development and facilitate the discovery of precise targets for treating and preventing AKI.